Information System applied in Construction Quality Control: A Mapping Study - Souza, Leander de Barros; Miceli Junior, Giuseppe; Choren, Ricardo (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2021: Anais do XVII Simpósio Brasileiro de Sistemas de Informação, 2021)
Civil construction has increasingly invested in techniques for quality assurance and control. Service inspection is a key activity in the quality control process is the inspection of services. It is executed by specialized professionals in order to register the quality of services. Through these inspections, it is possible to detect faults during construction. To get an overview of the approaches/techniques of information systems that have been used to support the inspection activity, a systematic mapping of the literature has been done. The literature mapping indicates the use of information systems to collect inspection data, mainly using technologies such as laser scanner, augmented reality, internal positioning and forms. Some works also use previous construction models, generated using BIM and 3D CAD models,to aid the inspection activity. Result analysis indicates that there are signs of immaturity within there search area, and it is recommended that existing systems are complemented with inspection issues tracking and quality control history features.